IMPLEMENTATION OF THE TSUKAMOTO FUZZY METHOD FOR INFANT FOOD RECOMMENDATIONS ACCORDING TO THE NEEDS AND AKG - Panjaitan, Zaimah; Suryanata, Muhammad Gilang; Ibnutama, Khairi (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2022)
Abstract: Choosing the right foods for babies to eat is easy. Age 0 to 5 years is a golden period for babies in their growth and development, both physically and intellectually. Incorrectly choosing foods that do not meet the needs can lead to the risk of obesity, while foods that do not meet the nutritional adequacy of infants can also cause stunting. An intelligent system taken from the knowledge of baby nutrition experts can be used as a solution to accompany parents in choosing the right food menu for babies during their growth and development. Fuzzy Tsukamoto can be used to group babies by age and weight, to decide which foods are suitable for consumption by the baby, based on the evaluation Images table compiled by the ministry of health as a guide for appropriate nutrition. This research resulted in a system that is able to assist parents in choosing the appropriate food menu for babies so as to prevent stunting.            Keywords: fuzzy tsukamoto; stunting; nutrition Abstrak: Memilih makanan yang tepat untuk dikonsumsi oleh bayi bukanlah hal yang mudah. Usia 0 sampai 5 tahun merupakan masa-masa emas bagi bayi dalam tumbuh kembangnya, baik fisik maupun kecerdasan. Salah memilih makanan yang tidak sesuai kebutuhan dapat menyebabkan resiko obesitas, sedangkan makanan yang tidak memenuhi angka kecukupan gizi bayi juga dapat menyebabkan stunting. Sistem cerdas yang diambil dari pengetahuan para pakar gizi bayi dapat dijadikan solusi pendamping orang tua dalam memilih menu makanan yang tepat bagi bayi di masa tumbuh kembangnya. Fuzzy Tsukamoto dapat digunakan untuk mengelompokkan bayi berdasarkan usia dan berat badan, untuk memutuskan makanan mana yang cocok dikonsumsi oleh bayi tersebut, berdasarkan tabel angka kecukupan gizi yang telah disusun oleh kementrian kesehatan sebagai panduan pemberian nutrisi yang sesuai. Dari penelitian ini dihasilkan sistem yang mampu membantu orang tua dalam memilih menu makanan yang sesuai bagi bayi sehingga dapat mencegah terjadinya stunting. Kata kunci: Fuzzy Tsukamoto; stunting; nutrisi